Kelimpahan dan Keanekaragaman Arthropoda dengan Teknik Pengendalian Berbeda Pada Pertanaman Padi (Oryza sativa L.) Varietas Ciherang - Taufiqullathif, Muhammad Hammad; Afifah, Lutfi; Saputro, Nurcahyo Widyodaru; Irfan, Budi (UNIVERSITAS LABUHANBATU, 2023)
Arthropods Abundance and Diversity Using Different Pest Control on Paddy Cultivation (Oryza sativa L.) Ciherang Varieties. Efforts to increase and maintain rice production face challenges due to attacks by arthropod pests. The most widely applied pest control by farmers is by using synthetic insecticides. However, synthetic insecticides affect the abundance of arthropods and are bad for the environment. This study aimed to obtain the lowest pest control technique on the abundance of arthropod pests, the best for natural enemiesand arthropod diversity, dominance, and evenness. The experiment design was Randomized Block Design (RBD) with 6 replications and 4 treatments including Untreated (UT), Combination Treatment (CT), Biointensive Treatment (BT), and Synthetic Treatment (St). Arthropod samples were taken 10 times from 1 â€“ 10 WAP using 3 traps namely yellow sticky trap, sweep net, and vacuum trap. The data were analyzed using variance, and if the results were significantly different, it was followed by the Least Significant Difference (LSD) at 5% level. The results of the analysis showed that ST gave the lowest abundance to the average abundance (741,83), yellow sticky trap (337.67) and sweep net (323.00) significantly different from other treatments. But was not significanty diffirent to the vacuum trap (81.17). The index values of diversity, dominance, and evenness for each role of arthropods are classified as medium, low, and medium. This indicates that the agroecosystem is in a state of balance.Â Keywords:Abundance, Diversity, Biointensive treatment,IPM, Arthropods